2016
DOI: 10.3390/molecules21101324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raw Material, Pressing and Glycosidase on the Volatile Compound Composition of Wine Made From Goji Berries

Abstract: This study investigated the effect of raw material, pressing, and glycosidase on the aromatic profile of goji berry wine. The free-run and the pressed juice of dried and fresh goji berries were used for wine production, whereas glycosidase was applied to wine after fermentation. Dried goji berry fermented wine exhibited much stronger fruity, floral, caramel, and herbaceous odors due to higher levels of esters, β-ionone and methionol. However, fresh berry fermented wine possessed stronger chemical notes due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Studies have shown that a mixture of components with a low ODT has coordinated enhancement, while a mixture with a high ODT will have masking properties [ 42 ]. In terms of the aromatic substances detected in this study, the ODTs of 42 of the compounds were found in the literature [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], 32 of which had an ODT less than 1 ppm. Among the six compounds that contributed most highly to the aromatic properties of the taxa, the aromatic thresholds of 5-methyl-1,3-dihydro-2H-benzimidazol-2-one and 4-pyrrolidinopyridine are unknown; the threshold of benzyl alcohol is 5; while the other three compounds (α-cedrene, β-cedrene, and linalool) exhibit extremely low thresholds (ODT < 1 ppm), indicating that these four compounds contribute greatly to the aromatic intensity.…”
Section: Discussionmentioning
confidence: 59%
“…Studies have shown that a mixture of components with a low ODT has coordinated enhancement, while a mixture with a high ODT will have masking properties [ 42 ]. In terms of the aromatic substances detected in this study, the ODTs of 42 of the compounds were found in the literature [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], 32 of which had an ODT less than 1 ppm. Among the six compounds that contributed most highly to the aromatic properties of the taxa, the aromatic thresholds of 5-methyl-1,3-dihydro-2H-benzimidazol-2-one and 4-pyrrolidinopyridine are unknown; the threshold of benzyl alcohol is 5; while the other three compounds (α-cedrene, β-cedrene, and linalool) exhibit extremely low thresholds (ODT < 1 ppm), indicating that these four compounds contribute greatly to the aromatic intensity.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, many organic substances of raw material can be metabolized to flavors (Zhao et al, 2017). For instance, goji rawmaterial played a primary role in flavor production, such as esters, benzenes, aldehydes/ketones, acids, alcohols and other volatiles (Yuan et al, 2016). Apart from these, raw material can regulate the growth and metabolism of microbes.…”
Section: Introductionmentioning
confidence: 99%
“…There are many goji derived-products on health food market, such as dried fruits, juice, goji wine and goji yoghurt. Many research papers were published focused on the phytochemical fingerprinting and antioxidant activity of these products [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%